GUUAM: ITS CURRENT STATE, RISKS, AND PROSPECTS - MATIICHIK, Iaroslav (CENTRAL ASIA AND THE CAUCASUS, 2004)
Cooperation within GUUAM (Georgia, Ukraine, Uzbekistan, Azerbaijan, and Moldova) has been made possible due to the spread in so-called “geopolitical pluralism” in Eurasia, which owes its existence to the disintegration of the Soviet Union and the ensuing decline in Russia’s influence. For Ukraine, these circumstances have led to a unique situation in which Kiev has the opportunity to make a name for itself in the geopolitical role of “East European communicator.” We can predict that GUUAM’s future place and role in the system of international organizations will be defined by what this union manages to achieve in its interaction with the European Union; the extent to which it can coordinate its own policy with U.S. strategy in the Caucasus and Central Asia; and the degree to which it can compete with other Eurasian international structures. In this context, it is important to understand that in the shorter term GUUAM could compliment interstate cooperation in the European vector, thus ensuring its own political stability, positive results in the economic sphere, and productive conflict-settlement measures. The foreign policy orientation of this organization hinges on its divergence with Russia’s integration plans, which makes them rivals, as well as geopolitical competitors in Eurasia. This is because they want to have a strategic advantage and gain control over the hydrocarbons of the Caspian Basin, over the goods and energy transportation routes along the Great Silk Road, and over the markets of the Central Asian and Caucasian countries. Cooperation within GUUAM is helping Ukraine to implement its policy aimed at stepping up Euro-Atlantic and European integration, as well as to develop international projects in formats which meet the new tasks, without ruining equal political and economic cooperation with Russia in the process.